Influences of Na2CO3, NaHCO3, K2CO3 on the rheological, water distribution, and microstructural properties of 5% long-chain inulin dough and quality of steamed bread. (15th February 2023) - Yue, Chonghui; Tang, Yu; Qi, Weiwei; Zhao, Yingyu; Liu, Pengfei; Hu, Jia; Song, Liqia; Luo, Denglin
Abstract: Inulin is rich in nutrition and can be used to produce functional flour products. Adding alkali to the dough system is an effective way to improve the quality of dough products. In this study, the effects of Na2 CO3, NaHCO3 and K2 CO3 on the rheology, water distribution, microstructure properties and steamed bread quality of 5% long inulin dough (FXL) were investigated. The addition of alkali improved the viscoelastic properties and the content of β-sheets in the FXL dough and made the weakly bound water move toward tightly bound water and free water. At the same time, the addition of alkali made the microstructure of the FXL dough tighter, but excess alkali (0.6 g/100 g) had a negative effect. The addition of alkali reduced the crystallinity. Alkali also gave steamed bread a pale yellow appearance, reducing volume and hardness compared to the control group. These results can contribute to a better exploration of the application potential of alkali in functional flour products to improve the quality of fortified flour products. Highlights: The addition of alkali increased the G′ and G″ of long chain inulin (FXL) dough. The addition of alkali causes the weakly bound water in the dough to migrate to tightly bound water and free water. The content of β-sheet structure increased to 31.09% when 0.4 g/100 g NaHCO3 was added. The addition of alkali reduces the hardness of the FXL steamed bread, it was most obvious in 0.2 g/100 g NaHCO3 group. Gluten network structure was affected by the amount of alkali added.